Viscoelastic polyborosiloxanes as artificial solid electrolyte interphase on lithium metal anodes. (20th August 2021) - Lennartz, Peter; Borzutzki, Kristina; Winter, Martin; Brunklaus, Gunther
Highlights: Synthesis of viscoelastic polysiloxanes with varying shear moduli up to 0.4 MPa. Application of polysiloxanes as protective coating on lithium metal anodes. Distribution-of-relaxation-times analysis reveals increased interphase resistances. Operando nuclear magnetic resonance spectroscopy quantifies Li deposit morphology. Beneficial effect of coating on deposit morphology at expense of higher resistance. Abstract: Lithium metal is considered as outstanding anode material due to its superior specific capacity and high redox potential, despite that non-uniform lithium deposition and dissolution upon charging and discharging yields formation of reactive high surface area lithium (HSAL) and a brittle, inhomogeneous solid electrolyte interphase (SEI). As counterstrategy, artificial SEIs such as protective polymer layers can be designed to control lithium deposition. Herein, viscoelastic polyborosiloxanes (PBS) with varying degree of cross-linking (maximum storage modulus of 0.4 MPa) are synthesized and coated on lithium metal. Operando 7 Li nuclear magnetic resonance spectroscopy illustrates that highly cross-linked PBS facilitates homogenous deposit morphologies, whereas merely cross-linked PBS does not show relevant effects compared to uncoated electrodes. Interphase analysis (impedance spectroscopy and distribution of relaxation times analysis) reveals increased interphase resistances for coated Li electrodes due to limited solvent uptake and provides a more detailed evaluation of resistive contributions from interphases compared to common equivalent circuit modeling. The beneficial effects of highly cross-linked PBS come at expense of higher resistance associated with a lower degree of swelling, hence emphasizing the complexity of Li deposition. Graphical abstract: Image, graphical abstract